2017
DOI: 10.1121/1.5009933
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring ice thickness and elastic properties from the measurement of leaky guided waves: A laboratory experiment

Abstract: The decline of Arctic sea ice extent is one of the most spectacular signatures of global warming, and studies converge to show that this decline has been accelerating over the last four decades, with a rate that is not reproduced by climate models. To improve these models, relying on comprehensive and accurate field data is essential. While sea ice extent and concentration are accurately monitored from microwave imagery, an accurate measure of its thickness is still lacking. Moreover, measuring observables rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…In a previous experimental work on wave propagation modes, using the very same set‐up and accelerometers, we demonstrated that QS0 and QA0 modes are found as expected, on top of a slower Stoneley (or quasi‐Scholte) mode propagating along the ice‐water surface (Moreau et al, ). The SH mode was absent likely because we recorded the vertical acceleration only.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…In a previous experimental work on wave propagation modes, using the very same set‐up and accelerometers, we demonstrated that QS0 and QA0 modes are found as expected, on top of a slower Stoneley (or quasi‐Scholte) mode propagating along the ice‐water surface (Moreau et al, ). The SH mode was absent likely because we recorded the vertical acceleration only.…”
Section: Methodssupporting
confidence: 73%
“…In addition to the work done by Moreau et al (), new experiments were conducted to characterize the propagation velocities and the attenuation of these modes for the specific needs of the present study. Accelerometers were linearly arranged and spaced by 5cm away from each other.…”
Section: Methodsmentioning
confidence: 99%
“…The present paper follows up on our work initiated at the laboratory scale to infer the thickness and mechanical properties of the ice from the observation of guided wave modes (Moreau, Lachaud et al, ). In a layer of ice floating on water, the wavefield is composed of modes that are of the same nature as those that propagate in a stress‐free plate, that is, the Lamb wave modes and the guided shear‐horizontal (SH) wave modes.…”
Section: Introductionmentioning
confidence: 99%
“…For higher values, the approximation no longer holds, and the dispersion branch of the QS mode starts to deviate from that of the flexural wave (Figure b). If frequency‐thickness is increased further, the energy on the vertical component of the displacement becomes progressively dominated by the QA 0 mode, the QS 0 mode becomes dispersive, and higher‐order modes become propagative (Moreau, Lachaud et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The general characteristics of guided P waves are similar to surface waves where the propagating waves are dispersive and their geometrical spreading behaves as O(r −1∕2 ). There are many applications of guided waves in seismology such as imaging low-velocity faulted-zone layers (Y. G. Li et al, 1999Li et al, , 2000, nondestructive evaluation and medical imaging with ultrasonic waves (Bochud et al, 2018;Moreau et al, 2017). The much slower arrivals in Figure 1a are the Rayleigh surface waves denoted as SW and propagate according to the S velocity of the associated layers.…”
Section: Introductionmentioning
confidence: 99%